2016
DOI: 10.3390/su8070619
|View full text |Cite
|
Sign up to set email alerts
|

Using Modified Remote Sensing Imagery to Interpret Changes in Cultivated Land under Saline-Alkali Conditions

Abstract: Abstract:Managing the rapidly changing saline-alkali land under cultivation in the coastal areas of China is important not only for mitigating the negative impacts of such land on the environment, but also for ensuring long-term sustainability of agriculture. In this light, setting up rapid monitoring systems to assist decision-making in developing sustainable management plans is therefore an absolute necessity. In this study, we developed a new interpretation system where symbols are used to grade and classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…These indoor experiments simulating the dynamic changes in water and salinity in saline-alkali soil revealed that after multiple irrigations of the soil column, the pH, conductivity, and total soluble salt content of the percolation samples were all higher than those of the initial water samples. With additional irrigation applications, these parameters gradually decreased in the percolation samples, consistent with the results in [ 23 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These indoor experiments simulating the dynamic changes in water and salinity in saline-alkali soil revealed that after multiple irrigations of the soil column, the pH, conductivity, and total soluble salt content of the percolation samples were all higher than those of the initial water samples. With additional irrigation applications, these parameters gradually decreased in the percolation samples, consistent with the results in [ 23 ].…”
Section: Resultssupporting
confidence: 90%
“…The pH, conductivity, and total soluble salt content values decreased overall, reflecting desalination in the simulation. When the 20–70 cm layer of the soil column was irrigated, the total salt content in the bottom layer of the soil column became 2.21–3.42 mg/L, representing a general decrease from initial values of 2.35–3.84 mg/L [ 23 ]. With increasing irrigation applications, the contents of all salt ions in the soil from Huanghua increased initially then decreased, reflecting resalinization and the considerable impact of soil moisture transport on K + , Na + , and Cl - .…”
Section: Resultsmentioning
confidence: 99%
“…However, from the history of reclamation in Zhoushan City, salt land or breeding ponds were built first and they gradually evolved into arable land thereafter with the improvement of soil. The tidal flats developed through concentrated reclamation in recent years may only be used for aquaculture [21,32]. Therefore, the newly increased aquaculture waters from tidal flats developed by reclamation should be identified beforehand as newly increased arable land.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating processed satellite data within hydrological models has become a promising approach for better and accurate quantifications of water resources in river basins [8,9].…”
Section: Introductionmentioning
confidence: 99%